MIGRASI BRANDING TRANSFORMASI IDENTITAS LEMBAGA PENDIDIKAN DARI "ACADEMIC-ORIENTED" KE "CAREER-READY" DI ERA DISRUPSI - Harisun Fuad haris; Moh. Imam Wahyudi; Ainur Rofiq (As-Sulthan Journal of Education, 2026)
This study aims to analyze the branding migration strategies of educational institutions in transforming their identity from an academic-oriented focus to career-ready readiness as an integrative solution to face labor market disruptions. Using a qualitative approach with an exploratory case study design, this research designates SMKN 1 Tegalsari as the material object through data collection techniques such as systematic observation, documentation, and in-depth interviews with key informants selected purposively, including school management, teachers, and students. The results of the study indicate that branding migration is carried out through three fundamental strategies: an epistemological shift that positions hard skills as the main branding currency, the implementation of micro-influencing strategies through students’ digital portfolios to build an organic narrative, and the utilization of the Teaching Factory ecosystem as evidence of authentic service reality. Theoretically, this study contributes to strengthening the literature on User-Generated Content and Experiential Marketing in the education sector, while practically providing strategic guidance for vocational institution managers in repositioning their identity to enhance brand equity and public trust amid global economic uncertainty.